Advertisement Remove all ads

Solve the following pair of linear equations by the substitution method. s – t = 3, s/3 + t/2 = 6 - Mathematics

Solve the following pair of linear equations by the substitution method.

s – t = 3

`s/3 + t/2 = 6`

Advertisement Remove all ads

Solution

s – t = 3   (1)

`s/3 + t/2 = 6`

From (1), we obtain

s = t + 3    (3)

Substituting this value in equation (2), we obtain

`(t + 3)/3 + t/2 = 6`

2t + 6 + 3t = 36

5t = 30

t = 6 (4)

Substituting in equation (3), we obtain

s = 9

∴ s = 9, t = 6

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

NCERT Class 10 Maths
Chapter 3 Pair of Linear Equations in Two Variables
Exercise 3.3 | Q 1.2 | Page 53
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×